Nonpolar vertical GaN-on-GaN p–n diodes grown on free-standing m-plane GaN substrates. (16th October 2018) - Fu, Houqiang; Zhang, Xiaodong; Fu, Kai; Liu, Hanxiao; Alugubelli, Shanthan R.; Huang, Xuanqi; Chen, Hong; Baranowski, Izak; Yang, Tsung-Han; Xu, Ke; Ponce, Fernando A.; Zhang, Baoshun; et al.
Abstract: We report nonpolar vertical GaN-on-GaN p–n diodes grown on m -plane free-standing substrates. Cathodoluminescence measurements showed that the nonpolar p-GaN had a high quality with very few deep-level states. The device exhibited good rectifying behaviors with a turn-on voltage of 4.0 V, on-resistance of 2.3 mΩ·cm 2, and high on/off ratio of 10 10 . The reverse current leakage was described by a trap-assisted space-charge-limited current conduction mechanism. The critical electrical field was calculated to be 2.0 MV/cm without field plates or edge termination. These results pave the way for development of novel nonpolar power electronics and polarization-engineering-related advanced power devices.